Cost Optimization Through Value Engineering and Risk Analysis in Industrial Building Retrofitting Projects - Trisamiyanto, Ferdinandus Danu; Susetyo, Budi (Journal La Multiapp, 2025)
Retrofitting projects in industrial facilities are often prone to delays and cost overruns due to various technical, logistical, and operational risks. These challenges include limited working access, delayed material delivery, and regulatory constraints, all of which can significantly affect project efficiency and cost performance. This study aims to optimize project costs by integrating value engineering and risk analysis methods in retrofitting construction. A mixed-method approach was employed, combining case studies with statistical analysis using Structural Equation Modeling – Partial Least Squares (SEM-PLS). Data were collected through surveys, expert interviews, field observations, and project documentation. The findings indicate that the integration of value engineering and risk analysis effectively reduces project costs without compromising quality. The application of value engineering resulted in an alternative solution using fire-rated drywall, which led to a cost saving of approximately IDR 5.36 billion or 9.63 percent of the original estimated cost. Additionally, the Life Cycle Cost (LCC) analysis showed that this alternative provided a more economical long-term solution, with a life cycle cost difference of 13.73 percent compared to the baseline material. These results highlight the practical benefits of integrating VE and risk management, offering a structured and data-driven framework for achieving cost-effective and sustainable outcomes in complex industrial retrofitting projects.